Modern weapons and military equipment for issue 4-2023 - Vučković, Dragan M. (Vojnotehnički glasnik / Military Technical Courier, 2023)
France’s Largest-Ever Drone Has Broken Cover; Russian Stealthy S-70 Okhotnik Attack Drone To Become Operational; Enhanced Version Of Russia’s Ka-52 Attack Helicopter Appears.